Artificial Neural Networks to Optimize the Conceptual Design of Adaptable Product Development - Feldhusen, J.; Nagarajah, A. (Cranfield University Press, 2009)
This paper describes an approach to apply Artificial Neural Network (ANN) to support the developer to optimize the conceptual design of Adaptable Product Development. The ANN learn from the previously mapping between the requirements and the product solutions. For a new development Process of an Adaptable Product the ANN analyse existing solution and sort them according to their probability of success. The advantages of this approach is on the one hand that ANN is able to identify the best suitable product solution for a new development order and on other hand the ANN automatically store the knowledge of the developer.
Organised by: Cranfield University
Keywords: Product Development Process; Engineering Design; Neural Network; Adaptable Products